ANALISIS PERBADINGAN KINERJA KEUANGAN DAN ABNORMAL RETURN SEBELUM DAN SESDUAH AKUISISI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014 - Ulfa Sakinah; Adhisyahfitri Evalina Ikhsan (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
The purpose of this study was to see a comparison of financial performance and abnormal return of companies before and after the acquisition of companies listed on the Stock Exchange in 2014. The number of samples used in this study were 10 companies, with a purposive sampling approach. The analysis technique used was paired sample t test and Wilcoxon signed rank test. The variables used are return on equity, current ratio, debt to equity ratio, total asset turn over, earnings per share, and abnormal return. Testing the hypothesis in this study using the sample t-test and Wilcoxon signed ranks test. The results of this study indicate that there are differences in the ratio of total asset turn over, while the return on equity ratio, current ratio, debt to equity ratio, earnings per share, and abnormal return there are no significant differences between before and after the company makes an acquisition.